Africa rising in an emerging world: an international marketing perspective. Issue 4 (13th July 2018) - Amankwah-Amoah, Joseph; Boso, Nathaniel; Debrah, Yaw A.
Abstract : Purpose: The purpose of this paper is to highlight important contemporary themes in international marketing strategy from the perspective of Sub-Saharan African firms. Design/methodology/approach: The approach adopted is a review and synopsis of the existing body of research on international marketing research in Sub-Saharan Africa, and a discussion of the manuscripts included in the special issue. Findings: International marketing in Sub-Sahara Africa is growing steadily, driven largely by rapid changes in socio-economic and demographic characteristics of consumers in this market. The growing appetite of multinational enterprises to explore new growth opportunities on this continent and the increasing intra-Africa cross-border transactions is driving unique approaches to international marketing that are predicated on using non-traditional means to produce, communicate and distribute products and services. Research limitations/implications: While the international marketing opportunities and challenges discussed in this paper are not exhaustive, the paper highlights important research themes that need consideration regarding international marketing research in Sub-Saharan Africa. Originality/value: This introductory paper emphasizes the unique international business landscape in Sub-Saharan Africa and discusses its international marketing strategy implications. The paper further draws attention to a number of unanswered research questions that require additional research, and thus bring Sub-Saharan Africa to international marketing scholarly enquiry.